Ethical dilemmas in research work in the discipline of management sciences - Matejun, Marek (Metody i techniki zarządzania. Inspiracje dla teorii i praktyki, 2020)
The aim of the publication is to identify, evaluate and classify ethical dilemmas that occur in research work conducted in the discipline of management sciences. On the basis of the literature review and the author’s own experience, a list of 11 activities that may be perceived differently from an ethical point of view was formulated. Their evaluation and classification was based on own empirical expert research on a sample of 102 scientists conducting research works in the discipline of management sciences. The results indicate an important, contextual diversity of ethical perceptions of the individual activities. At the same time, they allow to clearly distinguish 4 categories (classes) of ethical dilemmas in management science, including (1) involvement of respondents in research work, (2) researcher’s interference in the organisation’s activities, (3) dissemination of research results and (4) data acquisition in scientific research.